Analysis of Work Competence and Work Discipline on Performance Integrity within Organizational Settings under Transformational Leadership among Correctional Officers in Indonesia - Padmono Wibowo; Khansa Deryqa Prihadiansyah; Dari Aulia Qital; Dimas Danu Saputra (FOUNDAE (Foundation of Advanced Education), 2025)
Performance integrity of correctional officers in Indonesia has received increasing attention amid growing demands for professionalism and transparency, as well as various reports of procedural violations. This situation underscores the need to examine internal factors influencing integrity, particularly work competence, work discipline, and the role of transformational leadership. This study aims to investigate the relationships between work competence and work discipline on the performance integrity of correctional officers in Indonesia, assess the moderating effect of transformational leadership, and identify which factors most significantly impact integrity within correctional institutions. A quantitative approach was employed through a survey of 351 active correctional officers from various institutions across Indonesia, with data analyzed using PLS-SEM version 4.0.9.9. The findings indicate that work competence has a strong and significant effect on performance integrity, whereas work discipline and transformational leadership do not have significant effects, either directly or as moderators. These results emphasize that enhancing technical and functional competencies is key to improving integrity. This study is limited to quantitative analysis and does not encompass qualitative aspects, such as organizational culture, moral values, or interpersonal dynamics. Practically and theoretically, this research contributes to human resource management in correctional institutions by providing evidence-based insights and serving as a policy reference for implementing competency-focused strategies to strengthen officer integrity. The novelty of this study lies in its emphasis on individual capability as a more influential factor on integrity than structural mechanisms such as discipline or leadership style, challenging the common assumption that administrative discipline or leadership alone can foster integrity.